Developing an Effective Individual Amil Criteria - Mohamad Nor, Mohamad Naimi; Ishak, Suhaimi; Osman, Amirul Faiz (Global Academic Excellence, 2021)
Amil is the backbone of zakat activities which, in general, play a role in collecting and distributing zakat. However, some incidents of mismanagement involve amil raise concerns about the quality and role of amil. The question arises on the effectiveness of the amil and what should be done to minimize the case of mismanagement among amil. There should be some criteria that need to be met in the appointment of amil so that the appointed amil can fulfill the vision of the zakat institution. This study suggested five main criteria in determining effective amil, namely background of amil, appointment and replacement process, disciplinary action, expectations and targets: and reward. This paper contributes to the practice of forming good amil governance and can be used as a guide to amil and zakat institutions so that the objectives of zakat can be achieved